PELUANG PEMANFAATAN RUMPUT LAUT SEBAGAI AGEN BIOFILTRASI PADA EKOSISTEM PERAIRAN PAYAU YANG TERCEMAR - Wage Komarawidjaja (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2003)
Some observation result said that the worst of enviromental uality happened is primarily caused by mislead in the aim of develoment nature resources that only concern to economic growth. Therefore, the develoment of brakisth water ecosystem as an economic growth region should be relatedto the goal of enviromental waters uality management. To enhance this goal, the people utilizing brakish water ecosystem as aquaculture site may reduce organic pollution that is producedby their activities. Integrationof Gracilaria sp as a biofilter agent in aquaculture pond or in the wastewater treatment system is an alterantivetechnology for waters quality recovery enhancement.The initial success of this method in some countries has been reported. Therefore, if the biofiltration process in reducing organic pollution run properly, waters pollution in certain brakish ecosystemmaybe reduced.